Smart mixes for transboundary environmental harm / edited by Judith van Erp, Michael Faure, André Nollkaemper, Niels Philipsen. - Van Erp, Judith; Faure, Michael, 1958-; Nollkaemper, André; Philipsen, Niels, 1975- (Cambridge studies on environment, energy and natural resource governance., 2019)
This work offers a multidisciplinary approach to legal and policy instruments used to prevent and remedy global environmental challenges. It provides a theoretical overview of a variety of instruments, making distinctions between levels of governance (treaties, domestic law), types of instruments (market-based instruments, regulation, and liability rules), and between government regulation and private or self-regulation. The book's central focus is an examination of the use of mixes between different types of regulatory and policy instruments and different levels of governance, notably in climate change, marine oil pollution, forestry, and fisheries. The authors examine how, in practice, mixes of instruments have often been developed. This book should be read by anyone interested in understanding how interactions between different instruments affect the protection of environmental resources.